TAFSĪR ‘ILMĪ IN MADRASAH IBTIDAIYAH: FOSTERING A SPIRITUALLY AND SCIENTIFICALLY INTELLIGENT GENERATION - Tilotama, Azzahrah Ramaputri; Arif , Mahmud; Salkeri, Fadiah Khoirunnisa; Ramli, Radhita Maharani (Sekolah Tinggi Agama Islam Sadra, 2025)
Science and Islamic religion are closely related, especially in understanding the kawniyyah verses of the Qur'an that reflect natural phenomena. Islamic education plays a role in integrating these two aspects so that students understand science as part of Divine revelation. The tafsīr ‘ilmī approach in Madrasah Ibtidaiyah (MI) connects science with religious teachings through the interpretation of the verses of the Qur'an with a scientific perspective. This study aims to explore the application of tafsīr ‘ilmī in understanding the kawniyyah verses in MI and enrich students' scientific and spiritual insights. Qualitative methods with field research allow direct observation and data collection through observation and interviews. This approach helps identify the effectiveness and obstacles in the application of tafsīr ‘ilmī in the MI environment. Tafsīr ‘ilmī learning in MI connects science with religious teachings. Teachers explain natural phenomena such as the solar system, photosynthesis, or the creation of humans from a scientific perspective that is in line with the Qur'an. This approach encourages critical thinking, appreciation of science, and strengthens students' faith. The application of tafsīr ‘ilmī in MI forms a generation that is intellectually and spiritually intelligent. The integration of kawniyyah verses and scientific knowledge shows that religion and science complement each other. This study explores the supporting and inhibiting factors of its implementation and its impact on students' understanding. Thus, the results of the study are expected to provide real contributions in the development of learning methods based on the integration of religious knowledge and science in Islamic educational environments, as well as improving students' understanding of natural phenomena from a spiritual and scientific perspective.